'Speed advising' for medical students applying to residency programs: an efficient supplement to traditional advising. Issue 1 (1st January 2016) - McGrath, Jillian L.; Bischof, Jason J.; Greenberger, Sarah; Bachmann, Daniel J.; Way, David P.; Gorgas, Diane L.; Kman, Nicholas E.
Abstract : Background: Over time, Residency Match dynamics fluctuate with some specialties experiencing increases in medical student popularity. Academic departments with limited resources must devise methods for coping with increased demand for their specialty. Students perceive traditional programs on Match mechanics as inadequate. Subsequently, faculty are confronted with demands for more personal attention from more students. Objectives: We developed a strategy for providing specialty-specific residency match advising to large numbers of students. Methods: The 'speed-advising' session (SAS) was developed to address the common questions and concerns that medical students pose during the Match process and to provide advisees with a breadth of faculty perspectives. Two SASs were offered over a 2-week period. After the sessions, students and faculty were surveyed regarding their experience. Results: Twenty-six students pursued our specialty in the 2015 Match (26 of 234, 11.1%). Twenty-three (89%) participated in the SAS. Seventy-four percent of students (17 of 23) and all faculty completed the post-session survey. Students found the SAS to be informative, helpful and an efficient use of time. Common discussion topics included: career goals, to which programs and how many to apply, and how academic record impacts their likelihood of matching in our specialty . Students would have preferred more time with each faculty; however, most (77%) conceded that their questions were adequately answered. Faculty-favored speed advising over traditional advising (86%), primarily due to estimated time savings of 7.3 h per faculty member. Conclusions: In preparing students for the Match, specialty-specific speed advising offers an efficient supplement to traditional advising.